Speed Acquisition - Huang, Shiyang; Yueshen, Bart Zhou (Management Science, 2021)
Speed is a salient feature of modern financial markets. This paper studies investors’ speed acquisition together with their information acquisition. Speed heterogeneity arises in equilibrium, fragmenting the information aggregation process with a nonmonotone impact on price informativeness. Various competition effects drive speed and information to be either substitutes or complements. The model cautions the possible dysfunction of price discovery: An improving information technology might complement speed acquisition, which shifts the concentration of price discovery over time, possibly hurting price informativeness. Novel predictions are discussed regarding investor composition and their investment performance. This paper was accepted by Gustavo Manso, finance.